Dissimilarities Between Deweyan Pragmatism and Confucianism - Shen, Russell (Paideusis, 2012)
Over the past decade, numerous Deweyan philosophers have been arguing that Deweyan Pragmatism and Confucianism have significantly similar philosophical underpinnings and thus a Deweynised Confucian society is highly plausible. This article examines the social and historical backdrops against which Deweyan and Confucian thoughts were developed. It then explores the starkly contrasting and oftconflicting views of Dewey and Confucius on the purpose of education, the curriculum in schools, and the respective roles of teachers and students, morality, individuality, sociality as well as politics. The conclusion of this paper is that Deweyan Pragmatism is a context-specific, anti-dualist, and egalitarian theory whereas Confucianism is a transcendental virtue-oriented, universalist, and elitist philosophy. Therefore, any effort to promote the co-optation of Confucianism in Deweyan applications within Confucian civilisations, no matter how well intentioned, blocks the path to truth.